Neurological soft signs and brain network abnormalities in schizophrenia - Kong, Li; Herold, Christina; Cheung, Eric F. C.; Chan, Raymond C. K.; Schröder, Johannes (Schizophrenia bulletin, 2020)
Abstract. Neurological soft signs (NSS) are often found in patients with schizophrenia. A wealth of neuroimaging studies have reported that NSS are related to